The Impact of lncRNAs and miRNAs in Regulation of Function of Cancer Stem Cells and Progression of Cancer - Ghafouri-Fard, Soudeh; Hajiesmaeili, Mohammadreza; Shoorei, Hamed; Bahroudi, Zahra; Taheri, Mohammad; Sharifi, Guive (Frontiers in Cell and Developmental Biology, 2021)
Stem cells have two important features, namely the ability for self-renewal and the capacity to differentiate into some cell kinds with specialized functions. These two features are also present in cancer stem cells (CSCs). These cells have been detected in almost all kinds of cancers facilitating their tumorigenicity. Molecular cascades that control self-renewal of stem cells, namely the Wnt, Notch, and Hedgehog pathways have been suggested to influence CSCs functions as well. Moreover, non-coding RNAs can regulate function of CSCs. Function of miRNAs in the regulation of CSCs has been mostly assessed in breast cancer and hepatocellular carcinoma. miR-130a-3p, miR-600, miR-590-5p, miR-142-3p, miR-221, miR-222, miR-638, miR-375, miR-31, and miR-210 are among those regulating this feature in breast cancer. Moreover, miR-206, miR-192-5p, miR-500a-3p, miR-125, miR-125b, miR-613, miR-217, miR-194, and miR-494 regulate function of CSCs in hepatocellular carcinoma. DILC, lncTCF7, MUF, HAND2-AS1, MALAT1, DLX6-AS1, HOTAIR, and XIST are among lncRNAs that regulate function of CSCs. In the present paper, we explain the effects of these two classes of non-coding RNAs in the regulation of activity of CSCs.